Analysis of guides for development of municipal plans for integrated solid waste management - Costa, Alline Marchesin [UNESP]; Pugliesi, Erica (Assoc Brasileira Engenharia Sanitaria Ambiental, 2018)
The National Solid Waste Policy (NPSW) has established the Integrated Solid Waste Management Plans (ISWMP) as one of the instruments for solid waste management, and its formulation has conditioned to the access of the Union's resources, which has been designed for this objective. Technical training has emerged as the greatest difficulty faced by municipal managers in developing their ISWMP. Various organs has produced guides and manuals to meet such needs, in which five of them are analysed in this article. As a result, we have obtained a summary table of the studied model's characteristics, and it has demonstrated in most cases high load theoretical content with predominantly informative subject.
Keywords: solid waste; public policy; municipal management